Effect of Mixed Culture and Organic Loading Rate over Butanol Production from Biodiesel Waste in an Upflow Packed-Bed Reactor - Alves Tottoli e Silva, Cristina Aglaia [UNESP]; Adorno, Maria Ângela Tallarico; Ferreira, Filipe Vasconcelos; Peixoto, Guilherme [UNESP] (MDPI, 2024)
In this study, an upflow anaerobic packed-bed reactor (UAPB) produced biobutanol from the main byproduct of biodiesel plants, commonly known as glycerol. Currently, butanol production is mostly limited to pure cultures and sterilized feedstocks. Using glycerol wastes from biodiesel production demands a new paradigm because sterilization is not economically feasible for the elevated amount of glycerol generated by the biodiesel industry. Different microbial consortia were evaluated as inoculum sources to convert glycerol to butanol. In the first stage, operations were carried out with an average organic loading rate (OLR) of 13 g COD L−1 d−1. Kefir grains, sucrose auto-fermentation consortium, and heat-treated anaerobic sludge produced 16.7, 48.5, and 12.8 mg of butanol per gram of chemical oxygen demand (COD), respectively. Besides butanol production, a significant amount of ethanol (241.5 mg g−1 COD), acetate (30.3 mg g−1 COD), and butyrate (183.4 mg g−1 COD) were generated with glycerol processed by sucrose auto-fermentation consortium. In the second stage, the organic loading rates of 6.5, 13.0, and 26.0 g COD L−1 d−1 were applied to the UAPB reactor inoculated with sucrose auto-fermentation consortium. The OLR of 13.0 g COD L−1 d−1 yielded the highest production of butanol (41.5 mg g−1 COD) and generated other valuable co-products such as butyrate (246.1 mg g−1 COD), acetate (37.3 mg g−1 COD), and propionate (19.6 mg g−1 COD).
Keywords: anaerobic digestion; biobutanol; biodiesel; glycerol; inoculum; packed-bed reactor